1983
DOI: 10.1115/1.3138380
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Water Vapor Transport in the Human Upper Airways at Hyperbaric Conditions

Abstract: Heat and mass transfer mechanisms have been characterized in physical models of human cadaver airways to simulated depths of 305 m with various gas mixtures. Such characterizations offer a detailed understanding of the effects of environmental pressures, gas composition, and respiratory rates (RMV) on the body cooling capacity of the respiratory airways. Empirical heat transfer relationships in the form -Nu = AReNPr1/3 are derived for the oral and nasal passageways during inhalation and exhalation flows. -Nu, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The procedure to calculate vapor concentration in the air and tissue phases were as follows: First, mass transfer coefficients given by Eqs. (16), (20), (21), (27), and (28) were used to find an overall mass transfer coefficient given by Eq. (7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The procedure to calculate vapor concentration in the air and tissue phases were as follows: First, mass transfer coefficients given by Eqs. (16), (20), (21), (27), and (28) were used to find an overall mass transfer coefficient given by Eq. (7).…”
Section: Resultsmentioning
confidence: 99%
“…7 A similar finding was described by Miller et al 25 where they found a lower limit of Sh = 5.7 for convection-dominated flow and Sh = 8 for diffusion-dominated flow. Consequently, Bush et al 4 and Overton et al 30 made an adjustment to the model by Nuckols 27 for the lower limit of diminishing flow and proposed the following equation for the airphase mass transfer coefficient:…”
Section: Air-phase Mass Transfer Coefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…The "rst consists of the mouth and trachea; the second is the generations of the bronchial tree. Sherer & Hanna (1984) recommend the following heat transfer equation governing heat exchange process between inspired air and the surface of mouth/nose and trachea (Nuckols, 1981):…”
Section: Theory and Methodsmentioning
confidence: 99%